An Investigation Of Discourse Markers In Persian Male-Female Casual Conversation - Alami, Manizheh (2013)
Studies on spoken discourse have dramatically increased in recent years (Stenstrom, 1994; Tannen, 1984, 1991). The findings show that the features which were once called ‘empty’, ‘superfluous’ and ‘redundant’ are now considered as a crucial aspect of interpersonal communication. These linguistic elements called discourse markers (henceforth DMs) have been of great interest to researchers who are keen to study situated language because of their role in “demarcating discourse coherence and their potential for indexing social relationships”(Bolden, 2008, p. 102). Brinton defines DMs as “Phonologically short items that have no or little referential meaning but serve pragmatic or procedural purpose” (2008, p. 1).The present study is an attempt to investigate Persian men-women discourse in cross-gender interactions by focusing on the type, frequency of occurrence and function(s) of discourse markers in oral discourse. The qualitative and quantitative methods are employed to identify DMs and to specify their functions as they occur in Persian language. The particular dialect spoken by people living in Tehran, the capital of Iran, is the focus of investigation. Brinton’s (1996) binary classification is adopted as a theoretical framework in defining the functions Persian DMs have at the interpersonal and textual levels. Altogether 34 types of Persian DMs are identified and their functions are specified in this study among which na/na baba (no) occupies the top rank in the frequency list.